Impact of Auto industry and its spatial spillover effect on Alabama's Economic Growth and Development - Sooriyakumar, K.; Kinnucan, H. (Regional Science Inquiry, 2020)
This paper studies the effect of automobile production on Alabama's economy. A Spatial panel simultaneous equations model was developed using country data. The empirical findings suggest that automobile production increase the employment growth and per capital income growth of the countries which are closer to the automobile plant while other things equal, but reduce the population growth with closer distance to the automobile plant while other things equal. This may be due to the competition between automotive suppliers clustered around the automobile plant and real estate builders for land and other infrastructure facilities. This study also finds that jobs follow people and also people follow jobs. The existence of spatial lag indicates that growth of population; employment and per capital income are not only dependent on the characteristics of that country, but also on those of its neighbors. These interdependences provide the need of economic development policy coordination among the countries.
Keywords: Spatial effect; Automobile production; Spatial panel simultaneous equations model; Generalized Spatial Three-stage Least Squares